2019
DOI: 10.5027/andgeov46n2-3106
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived crustal damage zones associated with fault intersections in the high Andes of Central Chile

Abstract: Long-lived, high-angle fault systems constitute high-permeability zones that can localize the upward flow of hydrothermal fluids and magma throughout the upper crust. Intersections of these types of structures can develop complex interference patterns, which constitute volumes of damaged rock (networks of small-scale faults and fractures) where permeability may be significantly enhanced. This is relevant for understanding regional-scale structural controls on the emplacement of hydrothermal mineral deposits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This tectonohydrothermal environment has been observed in different regions of the Andes, where the intersections of major NNE thrust faults and ATF are hosts to giant ore‐porphyry deposits (Figure 1) (e.g., Chernicoff et al, 2002; Cox, 2005; Curewitz & Karson, 1997; Piquer et al, 2019; Rowland & Simmons, 2012; Sillitoe, 1997; Veloso et al, 2019). These points of intersection have also been deduced to impact geothermal reservoir development (Perez‐Flores et al, 2017; Sanchez et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This tectonohydrothermal environment has been observed in different regions of the Andes, where the intersections of major NNE thrust faults and ATF are hosts to giant ore‐porphyry deposits (Figure 1) (e.g., Chernicoff et al, 2002; Cox, 2005; Curewitz & Karson, 1997; Piquer et al, 2019; Rowland & Simmons, 2012; Sillitoe, 1997; Veloso et al, 2019). These points of intersection have also been deduced to impact geothermal reservoir development (Perez‐Flores et al, 2017; Sanchez et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…As discussed in section 2, these structures are considered discrete, reactivated, pre‐Andean faults, which exert a fundamental control in the location and development of volcanic features. They are enigmatic as their orientation with respect to the regional stress field makes them unfavorable to transport magma through the lithosphere (Cembrano & Lara, 2009; Chernicoff et al, 2002; Piquer et al, 2019; Sielfeld et al, 2019). The seismicity of Cls1 does not extend to the surface nor is there any surface expression of the structure, which supports the hypothesis that the ATF domain is contained within the basement lithology, and that they are of Pre‐Andean origin (Cembrano & Lara, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Escape‐tectonic behavior has been documented during the early Miocene (14 Ma) at 30°S, 300 km to the north of the study area (Giambiagi et al, 2017). Other evidences of Pliocene‐Quaternary strike‐slip deformation are found in the NE‐SW dextral and WNW‐ESE sinistral strike‐slip faults observed at the El Teniente porphyry copper deposits (~34°S) (i.e., Garrido et al, 1994; Piquer et al, 2016, 2019). Additionally, N37°E compression during the Quaternary (Lavenu & Cembrano, 2008) and strike‐slip focal mechanisms (Barrientos et al, 2004) in the Main Cordillera, to the east of the study area, consistently show a component of strike‐slip motion in the observed seismicity.…”
Section: Discussionmentioning
confidence: 99%